Asia and Pacific : Small States Monitor, April 2014: Volume 1, Issue 1 - Boyce, Shari (Miscellaneous Publications, 2014)
The work on the small states is an important component of the IMF's global policy agenda. Among the 36 member countries covered by the IMF Asia and Pacific Department (APD), 13 countries are developing small states-most of which are Pacific islands. As part of APD's ongoing effort to increase its engagement with regional small states and their development partners and enhance information sharing within the IMF, this issue marks the launch of the APD Small States Monitor, a quarterly bulletin featuring the latest economic developments, country notes from the most recent Article IV staff reports, special topics, past and upcoming events, and forthcoming IMF research on small states. In future issues, we will also host contributions from the authorities of small states and their development partners on key policy topics. Our goal is to exchange knowledge and deepen our understanding of the policy challenges these economies face to better tailor our policy advice.